Global Spatially-Disaggregated Crop Production Statistics Data for 2020 Version 1.0 - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
The 2020 SPAM (Spatial Production Allocation Model) products, encompassing crop area, yield, and production at a 5-minute grid resolution, have been developed by Zhe Guo, Shuang Zhou, and Liangzhi You. Employing a diverse range of inputs, IFPRI's Spatial Production Allocation Model (SPAM) utilizes a cross-entropy method to generate plausible estimations of crop distribution within disaggregated units. By transitioning data from broader units like countries and sub-national provinces to more granular units such as grid cells, SPAM unveils spatial patterns of crop performance, forming a global grid-scape where geography intersects with agricultural production systems. Enhancing spatial comprehension of crop production systems empowers policymakers and donors to effectively target agricultural and rural development policies and investments, thereby enhancing food security and fostering growth while minimizing environmental impacts.